The effect of using multimedia on the attitude of second grade intermediate students towards biology (Journal of the College of Basic Education, 2022)
The study aims to identify:* The effect of using multimedia on the attitude of second grade intermediate students towards biologyIn order to verify the objective of the research, the following null hypothesis was formulated:- There is no statistically significant difference at the level (0.05) between the mean scores of students of the experimental group who study topics in biology using multimedia and the scores of students in the control group who study the same subject according to the usual method according to the measure of attitude towards biology.